Melatonin and anticancer therapy interactions with 5-Fluorouracil - Cassim, Layla (Rhodes University, Faculty of Pharmacy, Pharmacy, 2008)
On the basis of clinical studies, some researchers have advocated that the neurohormone and antioxidant melatonin, shown to possess intrinsic anticancer properties, be used as co-therapy in cancer patients being treated with the antineoplastic agent 5-fluorouracil, as increased patient survival times and enhanced quality of life have been observed. The focus of this research was thus to investigate the mechanisms of this seemingly beneficial drug interaction between 5-fluorouracil and melatonin. Metabolism studies were undertaken, in which it was established that there is no hepatic metabolic drug interaction between these agents by cytochrome P450, and that neither agent alters the activity of this enzyme system. Co-therapy with melatonin is thus unlikely to alter plasma levels of 5-fluorouracil by this mechanism. Novel mechanisms by which 5-fluorouracil is toxic were elucidated, such as the induction of lipid peroxidation, due to the formation of reactive oxygen species; decreases in brain serotonin, dopamine and norepinephrine levels, possibly leading to depression; hippocampal shrinkage and morphological alterations and lysis of hippocampal cells, which may underlie cognitive impairment; and a reduction in the nociceptive threshold when administered acutely. All these deleterious effects are attenuated by the co-administration of melatonin, suggesting that the agent exhibits antidepressive and analgesic properties, in addition to its known antioxidative and free radical-scavenging abilities. This suggests that melatonin cotherapy can significantly decrease 5-fluorouracil-induced toxicity, but this may also exert a protective effect on cancer cells and thus compromise the anticancer efficacy of 5-fluorouracil. It was, furthermore, found that stimulation of indoleamine 2,3-dioxygenase activity, mediated by increases in superoxide anion and interferon-Î³ levels, may underlie resistance to 5-fluorouracil therapy. Melatonin was shown to increase superoxide anion levels in vivo, and this is believed to be by conversion to the metabolite and known oxidant 6- hydroxymelatonin. This highlights that the possible deleterious effects of melatonin metabolites should be studied further. Serum corticosterone levels and cytokine profiles are unaltered by both 5-FU and melatonin, suggesting that these agents may be used by HIV infected individuals without promoting the progression to AIDS. It can thus be concluded that melatonin co-therapy is potentially useful in countering 5-fluorouracil toxicity.
Keywords: Melatonin; Melatonin -- Therapeutic use; Antineoplastic agents; Fluorouracil; Fluorouracil -- Toxicology; Cancer -- Treatment